PENGGUNAAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN TEKS PUISI PADA PESERTA DIDIK KELAS X SMK PUI GEGESIK - Alina, Alina; Tobroni; Ade Hasanudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the discovery learning method on poetry text learning outcomes among 10th-grade students at SMK PUI Gegesik. Therefore, the hypothesis of this study is: the use of the discovery learning method in poetry text learning among 10th-grade students at SMK PUI Gegesik. This study is a population-based study. The research design used a pretest-posttest control group design, with a sample consisting of two classes: 20 students in the control class, XA, and 20 students in the experimental class, XB. Data collection included tests, observations, and documentation. All of this data was used to determine the effectiveness of the discovery learning method. Based on the analyzed data, the average learning outcome score for the control class, XA, using the Think-Pair-Share method was 71.50, while the average learning outcome score for the experimental class, XB, using the discovery learning method was 79.00. Then obtained t count = 4.781 and t table = 2.024, thus t count > t table, namely 4.781 > 2.024. thus means H0 is rejected and Ha is accepted. This shows the effectiveness of the use of the discovery learning method in learning poetry texts for class X students of SMK PUI Gegesik.